Enhancement of Astaxanthin Content in Mixed Culture of Dunaliella sp. and Azospirillum sp. under Light Intensity Treatment - Ria Amelia; Wulan Rahmani Akmal; Eko Agus Suyono (Faculty of Fisheries and Marine Universitas Airlangga, 2023)
Highlight Research The growth rate was higher when Chlorella was induced by Azospirillum brasilense. The carbohydrate content increased when combined with Azospirillum brasilense. Determination of astaxanthin accumulation in Haematococcus pluvialis. Define condition favoring astaxanthin accumulation in Haematococcus pluvialis. Abstract Dunaliella sp. is a potential natural source of carotenoid pigments such as astaxanthin, β-carotene, and lutein. Dunaliella sp. can also accumulate other valuable products such as glycerol and protein. Another species is Azospirillum sp., which is known as microalgal growth-promoting bacteria. These bacteria are often cultured with microalgae because they contain indole-3-acetic acid, which can significantly increase the growth of microalgae. This study aimed to examine the pigment content in mixed culture of Dunaliella sp. and Azospirillum sp. after being treated with different light intensity treatment. In this study, Dunaliella sp. were cultivated by mixing with Azospirillum sp. under light stress. Two treatments were performed at light stress intensity of 3000 and 6000 lx. Light intensity is widely used as an important parameter in cultivation, which can affect the growth and production of microalgal biomass. In addition, spectrophotometric UV-Vis based measurement was conducted to investigate every single pigment content in all treatments under light stress for eight days. The number of cells, carotenoid pigments, and astaxanthin had increased significantly. Pigments of chlorophyll a and chlorophyll b also significantly increased at lower light treatments. Based on the results, the bacterium Azospirillum sp. and high light intensity significantly increased the growth and cell division of microalgae. Therefore, the combination of Azospirillum sp. and light stress intensity in microalgae cultivation could increase the growth and pigment of Dunaliella sp.